Algeria : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
Algeria remains heavily dependent on the hydrocarbon sector and still maintains a sizable and inefficient state-owned enterprise sector. Against this background, the paper addresses two different issues with important implications for macroeconomic stability in Algeria. The paper proposes the replacement of directed credit to large loss-making public enterprises with temporary and explicit budget subsidies. It also shows that money, volume of imports, and weather conditions have a strong impact on price movements in the short term, whereas the exchange rate has none.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet